Identification of nitric oxide in mitochondria of myometrium cell - Danylovych, Yu.V.; Karakhim, S.A.; Kolomiets, O.V.; Danylovych, G.V.; Kosterin, S.O. (Вiopolymers and Cell, 2015)
Aim. To demonstrate the possibility of NO synthesis in intact myocytes of uterus. Methods. Confocal scanning microscopy method, NO-sensitive fluorescent probe DAF-FM, MitoTracker Orange CM-H2TMRos. Results. The basal production of NO in intact myocytes was shown using DAF-FM. Incubation of myocytes with NO donor – sodium nitroprusside (SNP) – led to an increase of the DAF-FM-T fluorescent signal. On the contrary, the addition of NO-synthase inhibitor – N-nitro-L-arginine (NA) – results in the reduction of fluorescent intensity. It was demonstrated colocalizition of specific probe for mitochondria MitoTracker Orange CM-H2TMRos and NO-sensitive dye DAF-FM. Conclusions. For the first time it has been demonstrated the presence of NO in smooth muscle cell mitochondria using laser confocal microscopy, NO-sensitive probe DAF-FM and specific marker of the functionally active mitochondria MitoTracker Orange CM-H2TMRos.